Carbohydrate and protein digestion on palm kernal cake by Mannanase BS4 and papain cocktail enzymes - SIW Rakhmani; Y. Pangestu; Arnold P. Sinurat; Tresnawati Purwadaria (Jurnal Ilmu Ternak dan Veteriner, 2015)
Supplementation of the mannanase BS4 enzyme on palm kernel cake (PKC) increased its metabolisable energy (ME), and supplementation with protease is expected to increase its protein digestibility. Therefore, the purpose of this research is to determine the optimum proportion of cocktail enzymes between BS4 β-mannanase (produced by Eupenicillium javanicum) and protease (papain) and their degradation activities on carbohydrate and protein of PKC. The β-Mannanase was produced by the mold through solid substrate fermentation (SSF) using coconut meal as the substrate. The papain was extracted from papaya latex (PL), collected by longitudinal incisions on unripe papaya fruit and oven dried overnight. The evaluation of enzyme cocktails for PKC hydrolysis was done at pH 5.8 and 40°C which are similar with poultry intestine condition and both enzymes are still active. The β- mannanase BS4 : papain were mixed with some proportions, i.e.: 100 : 0; 75 : 25; 50 : 50; 25 : 75 and 0 : 100% (by volume) in order to study the optimum cocktail composition ratio. The activities of β-mannanase towards gum locust bean was 86 U.ml-1 and papains PL activity was 18,000 U.g-1respectively. PL was chosen for synergistic reaction and compared with a commercial Merck papain (CMP, 20,000 U.g-1) as positive control. β-Mannanase BS4 showed carbohydrate digestion activity, and protein digestion activity was not detected. Papain showed protein digestion activity and no carbohydrate digestion activity. Enzyme cocktails of 50 : 50 from PL protease showed slightly increased in synergistic protein digestion activity in PKC. However, its reduction sugar production was much lower than 100 : 0 and 75 : 25. Amino acids production by enzyme cocktails 75 : 25 were higher than that of 100 : 0. As a result, the best volume composition of β-mannanase BS4 and papaya latex was 75 : 25 (v:v) or 14 : 10 (U:U).Key Words: Mannanase BS4, Papain, Cocktail-Enzymes, Palm Kernel Cake